2009
DOI: 10.1007/s12576-009-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive effects of the β2-agonist clenbuterol on expression of β2-adrenoceptor mRNA in rat fast-twitch fiber-rich muscles

Abstract: Administration of the beta(2)-agonist clenbuterol has been shown to reduce the expression of beta(2)-adrenoceptor (AR) mRNA in fast-twitch fiber-rich (extensor digitorum longus, EDL) muscle without changing that in slow-twitch fiber-rich (soleus, SOL) muscle in rats. However, the regulatory mechanism for muscle fiber type-dependent down-regulation of the expression of beta(2)-AR mRNA induced by clenbuterol is still unclear. Therefore, mRNA expression of transcriptional and post-transcriptional regulatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 45 publications
(83 reference statements)
1
25
0
1
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / l i f e s c i e plasticity via maintenance of muscle protein synthesis and degradation (Hinkle et al, 2002;Lynch and Ryall, 2008;Sato et al, 2008Sato et al, , 2010. Furthermore, several studies have demonstrated that glucocorticoids and the GR complex activate the transcription of the β 2 -AR gene through interaction with glucocorticoid response elements (GREs) in its promoter region (Cornett et al, 1998), leading to an upregulation of β 2 -AR expression (Hadcock and Malbon, 1988;Mak et al, 1995).…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…e l s e v i e r . c o m / l o c a t e / l i f e s c i e plasticity via maintenance of muscle protein synthesis and degradation (Hinkle et al, 2002;Lynch and Ryall, 2008;Sato et al, 2008Sato et al, , 2010. Furthermore, several studies have demonstrated that glucocorticoids and the GR complex activate the transcription of the β 2 -AR gene through interaction with glucocorticoid response elements (GREs) in its promoter region (Cornett et al, 1998), leading to an upregulation of β 2 -AR expression (Hadcock and Malbon, 1988;Mak et al, 1995).…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…Synthesized cDNA was added to a Power SYBR Green PCR Master Mix (Applied Biosystems) with 200 nM PCR primers (forward and reverse). The primer oligonucleotide sequences used for real-time quantitative PCR were as follows (Sato et al, 2010(Sato et al, , 2011: GR, 5′-TAC CAC AGC TCA CCC CTA CC-3′ (forward), 5′-AGC AGG GTC ATT TGG TCA TC-3′ (reverse); β 2 -AR, 5′-GAG CCA CAC GGG AAT GAC A-3′ (forward), 5′-CCA GGA CGA TAA CCG ACA TGA-3′ (reverse); 18S rRNA, 5′-GTG CAT GGC CGT TCT TAG TTG-3′ (forward), 5′-AGC ATG CCG AGA GTC TCG TT-3′ (reverse). Amplification was performed using an ABI PRISM 7000 Sequence Detection System (Applied Biosystems).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…In real-time quantitative PCR, synthesized cDNA was added to a power SYBR green PCR master mix (Applied Biosystems) containing 200 nM PCR primer (forward and reverse). The primer oligonucleotide sequences used for real-time quantitative PCR are described previously (Sato et al, 2010). Amplification was performed using an ABI PRISM 7000 Sepuence Detection System (Applied Biosystems).…”
Section: Rna Extraction and Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…We reported that administration of β 2 -agonist, clenbuterol (CLE: 4-amino-α (t-butylamino) methyl-3, 5-dichlorobenzyl alcohol), one of doping drugs, increased the weight of EDL muscle without changing that of SOL muscle (Sato et al, 2008). Further, administration of CLE decreased the density of β 2 -AR in fast-twitch muscles (Huang et al, 2000) and decreased the expression of β 2 -AR mRNA in EDL muscle without changing that in SOL muscle (Sato et al, 2008(Sato et al, , 2010. On the contrary, Cornett et al (1998) reported that glucocorticoids increased the transcription of β 2 -AR by acting toward glucocorticoid response elements (GREs) on β 2 -AR gene via glucocorticoid receptor (GR) using HepG2 cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fasting of the 3-, 8-, and 32-week-old rats was maintained for 2, 5, and 12 days, respectively. The animals were housed individually in stainless-steel cages at a controlled temperature (23-26°C) and a relative humidity of 45-60% with light-dark cycles [0700-1900 hours (light) and 1900-0700 hours (dark)] [21][22][23]. Animal chow (CE-2 cubic type; CLEA Japan, Tokyo, Japan) and once-boiled tap water were provided to the rats ad libitum.…”
Section: Experimental Procedures and Animal Carementioning
confidence: 99%